From Etest to Vitek 2: Impact of Enterococcal Linezolid Susceptibility Testing Methodology on Time to Active Therapy - Nguyen, Cynthia T. (Antimicrob Agents Chemother, 2020)
Different linezolid antimicrobial susceptibility testing (AST) methodologies yield various results. In 2018, we transitioned our linezolid AST methodology from the Etest to Vitek 2. We sought to evaluate the impact of this change on antibiotic use among 181 inpatients with vancomycin-resistant enterococcal (VRE) infections. The transition from Etest to Vitek 2 resulted in an increase in linezolid susceptibility (38% versus 96%; P < 0.001) and a reduction in time to active antibiotic therapy (3 versus 2.6 days; P = 0.007).